Polemik Pentafsiran Maqām Maḥmūd dan Penolakan Antropomorfisme dalam Kalangan Ahli Sunnah: Maqām Maḥmūd Polemic and the Denunciation of Anthropomorphism in Sunni Islam - Muhammad Noor, Umar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Contrary to the majority of scholars who interprets maqām maḥmūd (Quran 17:79) as intercession, the Hanbalites of Baghdad opine that the phrase means “Muhammad will be seated beside God on the throne.” They based their interpretation on an athar (saying) of an early Quran exegete, Mujāhid bin Jabr (d. 104H/722AD). Due to its apparent anthropomorphic feature, this standpoint caused a polemic that contributed to a violent clash in 317H/929AD. The objective of this article is to present and highlight Hanbalites’ stance in the maqām maḥmūd polemic and examine their acceptance of the athār of Mujāhid against overwhelming criticisms. The library research was applied to acquire data from various tafsīr, hadith, and theology literature then qualitatively analyzed. This study finds that Hanbalites’ advocacy to the athar of Mujāhid is not mainly based on the validity of the argument. Instead, it is driven by their anti-kalam sentiment to manifest the traditionalists’ supremacy after the abolishment of miḥnah khalq al-Qur’an. Reciprocating the Jahmiyya’s rejection of all ṣifāt traditions, the Hanbalites radically concede every anthropomorphic expression in traditions including those found in inauthentic hadith and athar. This inclination invites criticism from other Sunni scholars who emphasize authenticity as the most indispensable aspect of theological discourse. Despite immense efforts by modern neo-Hanbalis in defending the athar of Mujāhid, many of them have joined their adversaries in rejecting its reliability as theological proof.